Evaluation of mortality risk after COVID-19 vaccination, Utah 2021. Issue 18 (2nd May 2023) - Payne, Jessica R.; Bose, Srimoyee; Kubiak, Rachel W.; Nolen, Leisha D.
Highlights: Local vaccine safety data was evaluated through linkage of existing data sources. No additional mortality risk was identified among recipients of COVID-19 vaccines. This novel methodology could be readily used by other sub-national health agencies. Abstract: Introduction: In order to evaluate trends in death after COVID-19 vaccination we analyzed the timing of death relative to vaccination date and the causes of death in vaccinated Utahns in 2021. Methods: We matched people in the Utah immunization registry with documented COVID-19 vaccinations between December 18, 2020 and December 31, 2021 to Utah's 2021 vital statistics death records. Vaccinated people were categorized as having one, two, or ≥ three COVID-19 vaccine doses in a time-updated metric. We examined crude mortality rates by dosing groups in two-week intervals for all deaths, and by COVID-19 versus non-COVID-19 causes, within the 44 weeks following receipt of the most recent vaccine. Results: We identified 2, 072, 908 individuals who received at least one dose of COVID-19 vaccine of whom 10, 997 died in 2021. Only 17.5 % of the total vaccinated population was age 65+, while 80.9 % of those who died were over 65. In the four weeks following the first or second vaccination, all-cause mortality was low and then stabilized for the remainder of the evaluation period at a bi-weekly average of 33.0 and 39.0 deaths/100, 000 people for one and two doses, respectively. Typical seasonal variation in death was observed among those with two doses. Small sample size precluded analysis of those with ≥ three doses, but trends were similar. Conclusions: Mortality rates in the 44 weeks following the COVID-19 vaccination did not show trends suggesting an increase in mortality related to COVID-19 vaccination, reinforcing the safety of COVID-19 vaccines. This represents an accessible approach for local evaluation.